Tradisi Ngejot Sebagai Interaksi Komunikasi (Studi Kasus Pada Masyarakat Desa Dharma Agung, Kabupaten Lampung Tengah) - Noviari, Ni Luh Ayu; Kartika, Tina; Ashaf, Abdul Firman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The Ngejot tradition is a form of communication interaction involving the people of Dharma Agung Village, Central Lampung Regency. This tradition describes a unique communication pattern and has nuances of local wisdom. This research aims to document and analyze the Ngejot tradition as an expression of local community culture. Dharma Agung Village, as a research background, has a unique and diverse cultural richness. The Ngejot tradition is realized in the form of a series of communal activities, which involve the active participation of all residents. In the local community's understanding, Ngejot is not just a tradition, but also a symbol of togetherness and local wisdom. This research uses a qualitative descriptive approach by collecting data through observation, interviews and literature study. The data obtained from various sources was analyzed qualitatively, with a focus on communication patterns and cultural values ​​applied in the Ngejot Tradition. The research results show that the Ngejot tradition is not only a form of social interaction, but also a medium for conveying messages, norms and local wisdom values. Through this activity, the people of Dharma Agung Village can build close relationships, maintain harmony and preserve their cultural identity. This research contributes to further understanding of the role of the Ngejot Tradition as an important element in the communication interactions of the Dharma Agung Village community. It is hoped that the implications of this research will provide a more comprehensive picture of the richness of local culture in Central Lampung Regency and enrich the literature regarding communication interactions in the cultural context of Indonesian society.